Jamal Al-Banna`s position on Islamic legal rulings of Hijab and apostasy - Zakariyah, Habeebullah (Gupta Publications, 2017)
Interpretations on the meaning of Hijab (veil) and its legality in Islamic law have triggered attention in the recent years particularly in the Muslim Sunni world. Many Muslim scholars, organizations and academic institutions have made efforts to define the veil for Muslim women. There seems to be incoherent interpretations on the justification of use of Hijab as either compulsory or voluntary, considering the size and nature of its usage. Despite the effort of previous scholars in this regard, the pronouncement by Jamal Al-Banna that use of Hijab by Muslim women is not obligatory but mere Arab culture is a serious liberal legacy that requires urgent evaluation from Shariah perspective. Therefore, this paper aims to examine the concept of hijab and apostasy in Islam and see to what extent Jamal Al-Banna`s argument is consistent with the true Islamic perspective.